Kan miljöberikning öka baktriska kamelers (camelus bactrianus) användning av sitt utomhushägn - Morén, Sara (2021)
The Bactrian camel is a desert animal especially adapted to the harsh environment it lives in. It is part of the Camelidae family and exists as a wild species (Camelus ferus) and as a domesticated species (Camelus bactrianus). The wild Bactrian camel is listed as Critically Endangered by the International Union for Conservation of Nature (IUCN) and less than 1000 individuals are estimated to remain in the northwest part of China and Mongolia. The domesticated Bactrian camel exists in many parts of the world where it is used by humans for transportation, meat, milk and wool. Environmental enrichments are used to improve the management of animals in captivity and to increase the animals’ welfare. It can be used to increase the performance of species-specific behaviors, increase the animals use of its environment, or to prevent the development of abnormal or stereotypic behavior. The use of environmental enrichments is well established in many zoos worldwide and is an important part of their management routines. Furuvik is a zoo and amusement park in Sweden, with the zoo having about 200 animals of 40 different species. At Furuvik zoo there are four domesticated Bactrian camels that the zookeepers feel spend a lot of their time in their stable instead of in their outdoor enclosure. The purpose of this study was to examine if it was possible to get the camels at Furuvik to spend more time outside, by placing different environmental enrichments in their outdoor enclosure. The camels’ behavior was observed during three weeks in April using continuous focal observations and scan sampling methods. The first week was a control week where the zookeepers performed their regular routines, the second week was a treatment week where the enrichments were put in the enclosure and the third week no enrichments were used and the purpose of this was to see if the enrichments had any lasting effects on the camels’ behavior. The animals were observed during a total of three hours each day, distributed among the morning, day and afternoon. The results showed that placing enrichments in different parts of the outdoor enclosure, made the camels use the outdoor space in a more homogenous way. It also increased the time the animals spent outside during the morning but not during the day or afternoon. Individual differences were observed in the amount of time the camels spent in the outdoor enclosure and in how much the animals interacted with the enrichments. This study can be of help to the zookeepers at Furuvik, to see how changes in the camels’ regular routines might make them spend more time in their outdoor enclosure and increase their use of the outdoor space.